ASPECTS OF SERVICE COMPANY OPERATION AT EARLY STAGES OF MARKET DEVELOPMENT - Gennadievich Zharov, Vasily (Revista Inclusiones, 2020)
The paper explores the aspects of maintenance services of household appliances and changes in the industry after its emergence in the early 1990s and until the second decade of the 21st century. A highlight is the growing role played in the modern economies by services as a major economic sector and a key area of social life. The paper shows that the most acute problem of quality maintenance of household appliances arises in the period of market saturation with products of foreign manufacture. The author observes that the need to establish service centres to provide repair and maintenance services was felt by emerging appliance and electronics chains, and it came across as an additional competitive advantage in the fight for consumers, which fostered the intense development of service centres at the early stage. The paper specifies the typical business features of modern service companies handling household appliances, as well as the aspects of their relations with appliance manufacturers.